Microsatellites for Phytolacca acinosa (Phytolaccaceae), a traditional medicinal herb. (19th October 2017) - Cheng, Yueqin; Li, Pingping; Yang, Yi; Zhang, Jianhang; Yan, Fengming; Wang, Hongwei
Abstract : Premise of the study: Phytolacca acinosa (Phytolaccaceae) is a traditional Chinese herb with multiple medicinal uses and is an important pigment source. Due to excessive human harvesting, the population numbers and sizes have decreased dramatically. Methods and Results: Using an enriched genomic library, we developed and characterized 15 microsatellite primers for P. acinosa, 13 of which were polymorphic. The number of alleles varied from two to seven. The observed heterozygosity and expected heterozygosity per locus ranged from 0.267 to 1.000 and 0.331 to 0.743, respectively. All of the primers that were developed were also successfully applied in P. americana . Conclusions: These markers should be useful in probing the genetic diversity, genetic structure, and mating systems of P. acinosa, which could provide information about protecting and sustainably harvesting this species.